مستويات قلق الرياضيات وعلاقته ببعض المتغيرات لدى طلبة كلية المعلمين - د. هدى يونس خليل (PROSPECTIVE RESEARCHES, 2023)
The research aims at knowing the levels of mathematics anxiety among a sample of Teachers College Students, University of Mosul. The research studies the probable relation between the levels of anxiety according to some variables. It also aims at the investigation of differences between anxiety levels according to those variables. The sample consisted of (69) male and female students from the academic branches of mathematics, science and sociology in the teachers college. Mathematics anxiety measure was applied on them. The T-test for one sample was used to know the levels of anxiety among students according to the variables of sex and academic specialization. After calculating the arithmetic means, it was found that the differences were statistically significant and in favors of the hypothetical mean except for the branch of sociology in which the differences were not statistically significant. The T-test for two samples was used to know the differences in anxiety levels according to sex variable. The differences were not statistically significant. The analytical covariance to know the differences in mathematics anxiety levels according to the academic specialization variable was used. The differences were statistically significant .To specify the differences, Toke coefficient was used to know the relationship between the levels of mathematics according to sex and specialization By-Series test was used. The results showed that the relation between anxiety levels and sex is not statistically significant .The relation between anxiety levels and academic specialization was statistically significant.